Enhancing ethical food consumption: the impact of information framing on consumer preferences - Claudio Mirabella; Valeria Borsellino; Antonino Galati; Emanuele Schimmenti; Francesco Caracciolo (Agricultural and Food Economics)
Abstract Cases of unethical working conditions of agricultural workers, particularly in specialized rural regions of Europe such as Italy, have received increasing attention, calling for solutions to guarantee fair labor practices. This study investigates how Italian consumers respond to information about these issues by focusing on the framing of ethical attributes through a “Fair Labor” hypothetical certification designed to guarantee decent work and fair wages. Using a discrete choice experiment with three distinct information treatments, the paper explores the differential impact of negative versus positive framing of information on consumer decision-making. The results reveal that emotionally charged, negative information highlighting the consequences of unethical labor practices is particularly effective in amplifying consumer interest in ethical certifications. Conversely, positive framing, while still impactful, proves less influential in shaping preferences. Furthermore, trust in the certification is a critical factor in fostering favorable attitudes. These findings highlight the strategic importance of framing in promoting ethical certifications, offering valuable insights for policymakers and businesses aiming to enhance transparency and responsibility in agricultural supply chains while meeting the growing consumer demand for fair labor practices.